Exploring the willingness to pay for ecological tomatoes (Solanum lycopersicum L.) in Benin and Burkina Faso - Tapsoba, Parfait K.; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; Kestemont, Marie-Paule; Kabore Konkobo, Madeleine; Achigan-Dako, Enoch Gbenato (My University, 2022)
Agroecological food production and commercialization remain a major challenge in West Africa. This research aims to analyse consumers' willingness to pay (WTP) for agroecological tomatoes in Burkina Faso and Benin. For this, twelve Vickrey's second-best price auction sessions involving 360 consumers were organized. Based on their sociodemographic characteristics, a typology of consumers was established and a Double Hurdle model was used to analyse the determinants of the purchase decision and the value of their WTP. Three consumer clusters have been identified. Findings revealed that the perceived attributes of the ecological tomatoes fall into culinary/organoleptic, environmental, health and physical attributes. Moreover, the WTP for 1 kg of ecological tomatoes ranges from 400 to 4000 XOF. The results also showed that respondents' household tomatoes consumption has a positive influence on their purchasing decisions, while the number of known attributes as well as the country of residence of the respondent have a positive and significant influence on the value of their WTP. These results show a potential demand for ecological production and provide an opportunity for the implementation of a territorialized food system.
Keywords: Lancaster theory; Territorialized food system; Vickrey's experimental auction; Consumer typology; Cragg's double hurdle model